Situs Megalitik Tanjung Telang, Kabupaten Lahat: Kajian Bentuk Dan Fungsi. - Tama Maysuri; Zulkarnain Zulkarnain; Miftahuddin Miftahuddin (Diakronika, 2023)
Abstract This article is entitled Megalithic site Tanjung Telang, Lahat Regency: Study of Form and Function. This article aims to examine the from and function at the Tanjung Telang megalithic site, Lahat Regency, South Sumatra Province. This article uses the historical research method (historical method). This article uses the following stages: heuristics, source criticism, interpretation and historiography. The results of the research in this article say that in Lahat Regency there are many thousands of megalithic sites with various unique shapes and different sizes and have a certain meaning for each site found. Lahat Regency has a hilly area and a very fertile area, namely Bukit Selero which was trusted by the people in the past as a reminder that there is still a God above humans so humans must remain humble. Tanjung Telang Village, West Merapi District, Lahat Regency, South Sumatra, Found megalithic cultural relics inthe form of the Tanjung Telang Human Statue, Megalithic Flat Stone and Menhirs. The heritage site in the form of megalithic culture is located with in the environment of West Merapi 2 Junior High School, in the highlands (hills), shrubs, and is located in the community’s coffe garden.